Results of Agricultural Reforms Being Implemented in the Khorezm Region (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article presents the results of reforms in agriculture of the Khorezm region according to the State program for the implementation of melioration measures and the financial resources spent. An analysis of changes in agriculture over previous years according to statistical data and the significance of the achieved results in the socio-economic development of the region is made. Proposals and recommendations for the development of agricultural production are developed.